Aplicação e alcance do princípio da intervenção mínima do Poder Judiciário nas normas coletivas: análise e compatibilidade com os direitos fundamentais - Schnitzlein, Sílvia Figueiredo Araújo (2023)
By descriptive, scholar’s opinion and bibliography, the present study addresses controversial about article 8º, paragraph 3º of Labor Code, limits imposed to the Judiciary by such article and possible interpretations to it, seeking for the one that is compatible with fundamental rights. The present study is based on especially theoretical aspects, through the analysis of legislation, scholar’s opinions, and the current precedents on the subject and associated aspects, mainly of a labor perspective and its interaction with constitutional and civil aspects on the matter. It analyzes the labor context in which the above-mentioned article is inserted and its association with rules about collective bargaining agreements and with the articles 611-A and 611-B of the Labor Code, in addition to the relation with the article 104 of the Civil Code and with the constitutional rules and principles. The purpose of this dissertation is to conclude what would be the best interpretation to be given to the article 8, paragraph 3 of the Labor Code, focusing on, one side, to avoid its unconstitutionality declaration and, on the other side, to ensure that it is aligned with fundamental rights